Pharmacological effectiveness of рeritol and soluble аspirin in the treatment of piglets, suffering from gastroenteritis - Шатохін, П. П.; Супруненко, К. В.; Каришева, Л. П. (Scientific Progress & Innovations, 2015)
We dealed with a subject of piglets' gastroenteritis treatment. The aim of our study was ANNOTATIONS № 3 • 2015 • ВІСНИК Полтавської державної аграрної академії 207 to use in the treatment of patients piglets preparations, namely serotonin antagonist – peritol and drugs from the group of salicylates – water soluble form of aspirin. It was established that the drugs we used exhibit diverse effects on the pigs, in particular, on the performance of erythropoiesis, some indicators of antioxidant system and thyroid concentration of hormones. According to the results of experiments determined the therapeutic efficacy of our proposed treatment regimens.